Impact of extending prevention of postoperative nausea and vomiting for cancer surgical patients in the PACU: a before and after retrospective study - Cyrus Motamed; Gr..goire Weil; Jean Louis Bourgain (Brazilian Journal of Anesthesiology, 2022)
Backgrounds: Procedures for Postoperative Nausea and Vomiting (PONV) prevention are mostly based on identification of the risk factors before administering antiemetic drugs. The purpose of this study was to evaluate the impact of the extended use of antiemetic on the PONV in the Postanesthetic Care Unit (PACU). Methods: Two separate 4-year periods (2007...2010, P1, and (2015...2018, P2) were evaluated. During P1, the protocol consisted of dexamethasone and droperidol for patients with a locally adapted high PONV score, followed by ondansetron for rescue in the PACU. For Period 2, dexamethasone (8 mg) and ondansetron (4 mg) were administered in patients under general or regional anesthesia, or sedation longer than 30 minutes, while droperidol (1.25 mg) in rescue was injected in cases of PONV in the PACU. An Anesthesia Information Management System was used to evaluate the intensity score of PONV (1 to 5), putative compliance, sedation, and perioperative opioid consumption upon arrival in the PACU. Results: A total of 27,602 patients were assessed in P1 and 36,100 in P2. The administration of dexamethasone and ondansetron increased several fold (p < 0.0001). The high PONV scores were more improved in P2 than in P1, with scores (3+4+5) for P1 vs. P2, p < 0.0001. Overall, 99.7% of the patients in P2 were asymptomatic at discharge. Morphine consumption decreased from 6.9..1.5 mg in P1 to 3.5 .. 1.5 mg in P2 (p < 0.0001). Discussion: The extension of pharmacological prevention of PONV was associated with a decrease in the intensity of severe PONV. However, uncertainty regarding confounding factors should not be ignored. IRB: n.. 92012/33465